2019
DOI: 10.3390/cancers11040453
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Inhibition of Cytoprotective Autophagy Augments the Efficacy of Withaferin A in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related mortality, and despite recent advances in early diagnosis and therapeutics, HCC related morbidity and mortality rate continue to rise. Clearly, it is imperative to develop novel effective therapies for HCC to improve long-term survival of HCC patients. We found that Withaferin A (WFA), a bioactive compound derived from Withania somnifera, is an effective agent for HCC inhibition. Interestingly, we observed that in addition to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…In this work, Rg5 induced autophagy in breast cancer cells, which was demonstrated by the formation of autophagosomes observed by TEM, the upregulation of LC3-II, Beclin-1, Atg5, and Atg12 expression and the downregulation of p62 expression. Characterized by two main features, namely, the involvement of cytoplasmic material and culmination with lysosomal degradation, autophagy is a multistep process [35]. Rg5 treatment increased the level of LC3B puncta, and microscopic evaluation of tandem GFP-RFP-tagged LC3B in MCF-7 cells demonstrated that Rg5 induced the occurrence of autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, Rg5 induced autophagy in breast cancer cells, which was demonstrated by the formation of autophagosomes observed by TEM, the upregulation of LC3-II, Beclin-1, Atg5, and Atg12 expression and the downregulation of p62 expression. Characterized by two main features, namely, the involvement of cytoplasmic material and culmination with lysosomal degradation, autophagy is a multistep process [35]. Rg5 treatment increased the level of LC3B puncta, and microscopic evaluation of tandem GFP-RFP-tagged LC3B in MCF-7 cells demonstrated that Rg5 induced the occurrence of autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple view-fields were examined and representative cells from 3 view-fields were photographed. For puncta, at least 50–100 cells/sample were counted in triplicates 45 , 77 , 78 .…”
Section: Methodsmentioning
confidence: 99%
“…Upon exposure to WA, MDA-MB-231 and MCF-7 breast cancer cells underwent autophagy, which was confirmed by analysis of acidic vesicular organelles and cleavage and recruitment to autophagosomes of LC3-II [56] . WA-induced autophagy was shown to be cytoprotective in hepatic cells, and by inhibiting its cytoprotective effects with chloroquine, tumor cells became more responsive to therapy [57] . Table 3 summarizes the WA-induced autophagic response in different cancer models.…”
Section: Dhc and Capmentioning
confidence: 99%
“…Lung WA and pemetrexed, cisplatin, or gemcitabine Synergistic effect of WA and pemetrexed, cisplatin, or gemcitabine. WA downregulated mTOR/STAT3 signaling Siddharth et al [57] 2019 Cell culture, Huh7, HepG2, MHCC97H, MHCC97L…”
Section: Ws480 Ht-29 Hct-116 Ncm-460mentioning
confidence: 99%